Analisis Penggunaan Pembayaran Paylater terhadap Perilaku Konsumsi Masyarakat dalam Pandangan Islam - Nugroho, Anton Priyo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The market has experienced unprecedented growth in recent years, which has significantly impacted the way consumers conduct their consumption behavior by offering a new payment method called PayLater. PayLater is intended to direct people to consumptive behavior in purchasing products because of the payment process later. In fact, Islam has certain principles regarding consumption activities, including the prohibition of waste in personal and collective consumption. So, in Islam, consumption must be based on needs, not just to fulfill desires which of course have no end. This research aims to determine the effect of using PayLater on Islamic consumption behavior by using three X variables including Convenience (X1), Trust (X2) and Lifestyle (X3). This research uses a quantitative approach with a population of 150 respondents. The data collection technique used was by distributing questionnaires online via Google Form. Data analysis techniques use the Classic Assumption test, Multiple Linear Regression Test using the t test, F test and coefficient of determination test. The results obtained from this research using the SPSS program obtained results from the coefficient of determination test of 94% while the remaining 6% was influenced by external variables. Multiple linear regression of the variables Convenience (X1), Trust (X2) and Lifestyle (X3) which have an influence on the PayLater Usage Behavior variable (Y).